2002
DOI: 10.1002/jemt.10009
|View full text |Cite
|
Sign up to set email alerts
|

Microvasculature in gingivitis and chronic periodontitis: Disruption of vascular networks with protracted inflammation

Abstract: Gingivitis occurring when bacterial plaque accumulates in the gingival crevice provides a convenient and interesting model for chronic inflammation in humans. In some patients, gingivitis progresses to the destructive lesion of periodontitis, involving the formation of periodontal pockets. The basis for pocket formation and progression is not as yet clear, although neutrophilic polymorphonuclear leukocytes (PMN) appear to play a protective role. Vascular changes appear to either facilitate or inhibit PMN funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 122 publications
4
74
0
1
Order By: Relevance
“…Because of the degradation of proteins of epithelial cell-cell junctional complexes, P. gingivalis may be able to invade and spread in deeper structures via a paracellular pathway (38). The periodontal pocket is a highly vascularized tissue in close proximity to the bacterial biofilm (15) that is separated from endothelial cells by one to two epithelial cells and a negligible layer of extracellular matrix (71). It has been suggested that in periodontitis, proapoptotic signals, such as direct toxic effects of bacterial products from the nearby plaque, at times overwhelm the usual antiapoptotic functional signals that maintain periodontal vessels (71).…”
mentioning
confidence: 99%
“…Because of the degradation of proteins of epithelial cell-cell junctional complexes, P. gingivalis may be able to invade and spread in deeper structures via a paracellular pathway (38). The periodontal pocket is a highly vascularized tissue in close proximity to the bacterial biofilm (15) that is separated from endothelial cells by one to two epithelial cells and a negligible layer of extracellular matrix (71). It has been suggested that in periodontitis, proapoptotic signals, such as direct toxic effects of bacterial products from the nearby plaque, at times overwhelm the usual antiapoptotic functional signals that maintain periodontal vessels (71).…”
mentioning
confidence: 99%
“…diseased periodontal pocket, there is a close proximity between the bacterial biofilm and endothelial cells, which can lead to endothelial cell damage (59). Furthermore, there is evidence for the presence of apoptotic cells in periodontitis (19,34,51,57).…”
mentioning
confidence: 99%
“…Chapple et al (2000) found that vascular expansion in periodontal pocket was related to CP progression and the thickened basement membrane of capillaries and venules represented an evidence of angiogenic activity during inflammation. Vascular response to inflammation includes angiogenesis and capillaries dilation (Pinchback et al, 1996;Chapple et al, 2000;Zoellner et al, 2002). The present study demonstrated that Vv of blood vessels in CP gingival tissues was significantly higher than that of healthy subjects.…”
Section: Discussionmentioning
confidence: 45%